STRATEGI MENINGKATKAN KEBERDAYAAN KELUARGA MISKIN PEDESAAN DI KABUPATEN LAHAT PROVINS! SUMATERA SELATAN (Strategy to promote capability of poor rural families in Lahat District South Sumatera Province) - Ramli Toha; Amiruddin Saleh (Sosio Konsepsia, 2009)
Poor rnral families were part of rural society which need to improved was resources, in order that they could efford to run family function, had creativih; in economy, social, physicology and sociology, that kind of creativity, poor families hopefully could build harmonies in their life. These research had correlation descriptive character which purposes; (a) analyzing factors that cause poverty, (b) analyzing characteristic of poor families from social economy aspect, physical characteristic, physicologi; characteristic and sociology characteristic (c) knowing and analyzing dependabilih; pattern of triggering factors and characteristic of poor families in promoting capabilihJ of poor families (c) building strategies to promote capability of poor families according to trigger factor and characteristic of rural poor families. Research result showed internal environment and external factors which influenced capability of poor families in rural area. Trigger factor that emerge poor families were, poverty was already inherit by their elderly, because their elderly didn't have wide farmland, low education background (they didn't pass the elementan; school in average), didn't have other skills beside farming. There were obvious correlation among social economy, social capital, local intelegence and capability of poor families. According to data and information that acquired from the research. Therefore strategic concept was made and pointed, empowering competence of personal implementer of government program in subdistrict level empowering poor families competence, promoting poor families participation in government and private programs that operation in rural area. Build poor families network with business world in marketing their Jann product and giving them facilitation to get capital, seeds and tools that according to compete development that given to poor peoples.